Laparoscopic Hysterectomies: Our 10 Years Experience in a Single Laparoscopic Center - Bettaiah, Ramesh (J Obstet Gynaecol India, 2015)
STUDY OBJECTIVE: To evaluate the association between outcomes of laparoscopic hysterectomy with respect to clinical factors, intraoperative variants, and post-operative complications. DESIGN: The study conducted was retrospective (Canadian Task Force Classification II-1). SETTING: The set used in this study was a gynecological laparoscopic centre. PATIENTS: The present study included 858 women who underwent laparoscopic hysterectomies with or without bilateral/unilateral salpingo-oophorectomy, from December 2004 to May 2014. INTERVENTIONS: Eight hundred and sixteen patients underwent total laparoscopic hysterectomy, 14 patients underwent subtotal laparoscopic hysterectomy, 20 patients underwent laparoscopic-assisted vaginal hysterectomy, and 8 patients underwent laparoscopic radical hysterectomy with bilateral pelvic lymph node dissection. MEASUREMENTS AND MAIN RESULTS: All surgeries were performed by the same surgeon, using the same surgical technique. The medical records were reviewed, and data were collected with respect to age, indications, type of surgery performed, intraoperative variants, and post-operative complications. Patient average age was 44.9 ± 6.2 years. Most common indication for benign TLH was leiomyoma of 54.4 %. Indications for laparoscopic radical hysterectomy were early stage endometrial cancer (n = 5) and early stage cervical cancer (n = 3). The maximum uterine size operated on was from 20–26 weeks, 4.9 % (n = 42). 9.7 % had previous abdominopelvic surgery. Fifty three % underwent unilateral/bilateral salpingo-oophorectomy. Conversion rate was 0.93 % (n = 8). The minimum and maximum operating time during the total study period was 20 min–2 h. The major complication rates were 0.9 % (n = 8). The hospital stay was not more than 2 days. CONCLUSION: In our experience of 858 laparoscopic hysterectomies, 850 were done for benign indications, and 8 done for malignancies. TLH can be performed more safely and under vision, with less blood loss, early post-operative recovery, less post-operative infection, and less complication rate.